Factors related to the development of pneumonia associated with ischemic stroke - Alexis Suárez Quesada; Alexis Álvarez Aliaga; Andrés Quesada Vázquez; Julia Matilde Pupo Jiménez (Medisur)
Background: stroke-associated pneumonia is related to increased mortality, decreased functional recovery and prolonged hospital stay, with the consequent economic impact on health services. Objective: to identify the risk factors for the development of pneumonia associated with ischemic stroke. Methods: analytical observational study, prospective cohort, with 725 patients diagnosed with ischemic stroke, treated at the Carlos Manuel de Céspedes Hospital (Bayamo, province of Granma), from January 2015 to July 2019. The association of the variables Sociodemographic, personal pathological history, toxic habits, stroke conditions, dysphagia, biochemical and immunonutritional markers with the development of pneumonia associated with ischemic stroke were determined using binary logistic regression. Results: Of the total number of patients studied, 21.5% developed pneumonia associated with stroke. The main risk factors were dysphagia (OR= 13.9), COPD (OR= 13.9) and a score on the NIHSS scale ≥ 12 points (OR= 8.31). The most frequently isolated germ was Enterobacter aerogenes (26.3%). In relation to the fulfilled clinical criteria, 89.1% presented leukocyte alteration. Conclusion: the logistic regression model made it possible to identify the factors related to the development of pneumonia associated with ischemic stroke based on data available on a regular basis in healthcare practice.